Impacts of Climate Change and Ice Conditions on Microbial Food Web Dynamics in the Barents Sea - Peter Lavrentyev (Arctic Data Center, 2013)
This study aims to examine the relationships between the planktonic food web of the Barents Sea and changing sea-ice conditions. It would focus on the role of microzooplankton (MZP; 20 - 200 um in size), which have been suggested to be more important herbivores than the larger copepods in the tightly coupled food web of the Barents Sea, and would address the following questions: 1. What is the spatial distribution of phytoplankton and MZP standing stocks in response to the change in ice cover and sea temperature? 2. Do distinct water masses and ice cover determine the taxonomic composition of MZP in the Barents Sea? 3. What is the capacity of MZP to use primary production under different sea temperature/ice conditions? 4. What is the relative importance of heterotrophic protists in pelagic copepod diet under different ice/sea temperature/bloom combinations? The PIs propose to address these questions by conducting five research cruises in the Barents Sea over three years to capture seasonal and interannual variability in microbial distribution and dynamics. Detailed data will be obtained on horizontal and vertical distributions of phytoplankton and MZP using a towed, high-resolution plankton survey system. These data will be related to hydrographic (ice cover, sea temperature, stratification), hydrochemical, and other biological variables. The program will directly involve a postdoctoral researcher, two graduate students, and several undergraduates at an urban, minority-serving institution. In addition, the project team includes a professional science educator who will coordinate the production and dissemination of curriculum materials for grades 7-12 and the conduct of teacher workshops.